Interrelationships and evolution of basal theropod dinosaurs - Rauhut Oliver W M (London Palaeontological Association, 2003)
This paper presents a phylogenetic analysis of all theropods, but focuses on the basal members of this clade. It provides the inclusion of Eoraptor and herrerasaurids in the Theropoda but differs from other recent studies in two main aspects. 1.The taxa
Keywords: Dinosaurs